Supporting, Promoting, Respecting and Advocating: A Scoping Study of Rehabilitation Professionals’ Responses to Patient Autonomy - Blackburn, Emilie; Durocher, Evelyne; Feldman, Debbie; Hudon, Anne; Laliberté, Maude; Mazer, Barbara; Hunt, Matthew (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
Background: Autonomy is a central concept in both bioethics and rehabilitation. Bioethics has emphasized autonomy as self-governance and its application in treatment decision-making. In addition to discussing decisional autonomy, rehabilitation also focuses on autonomy as functional independence. In practice, responding to patients with diminished autonomy is an important component of rehabilitation care, but also gives rise to tensions and challenges. Our objective was to better understand the complex and distinctive ways that autonomy is understood and upheld in the context of rehabilitation care by reviewing how autonomy is discussed in the rehabilitation literature. Methods: We conducted a scoping review addressing issues of autonomy in the context of mental and physical rehabilitation. Our process followed three sequential steps. We extracted and analyzed bibliometric information. We then examined how autonomy was defined and conceptualized. Finally, we examined how the articles discussed the roles of rehabilitation health professionals in responding to patient autonomy. Findings: The articles include 16 empirical reports, 17 case studies and 30 theoretical papers. The most common conceptual accounts of autonomy drew upon principlism, rights-based and legal analyses, and relational/social approaches. We identified four broad approaches for responding to patient autonomy: supporting, promoting, respecting and advocating. Conclusion: This review helps clarify some of the ambiguities and conceptual distinctions underlying discussions and practices related to autonomy in rehabilitation. It also draws attention to a wide range of activities that health professionals can undertake with the goal of supporting, promoting, respecting and advocating for patient autonomy in rehabilitation care.